Tari Sesandaran Di Griya Delod Pasar Desa Adat Intaran; Kajian Bentuk, Fungsi Dan Makna. - Sidhi, I Putu Gede Serana Asta; Trisnawati, Ida Ayu; Widnyana, Kompiang Gede (Jurnal IGEL : Journal Of Dance, 2024)
The Sesandaran dance at Griya Delod Pasar is a bebali dance that is sacred to the people and was born in the Intaran Traditional Village. This Sesandaran Dance is the same as the Telek Dance which uses a white tapel or mask and has a subtle character. Of course, the Sesandaran Dance which is located at Griya Delod Pasar is created with its own characteristics and identity. These characteristics exist at the beginning, the form of the dance. This Sesandaran Dance Research uses a qualitative research method with a descriptive qualitative approach. The research data was obtained through several stages, namely observation, structured and unstructured interviews, and indirectly through library research and documentation studies. The final task of the independent learning program in the dance study program this time the researcher chose the object of the Sesandaran Dance at Griya Delod Pasar as the object of research.ance, the function and meaning of the dance. The research results obtained that the Sesandaran Dance at Griya Delod Pasar is a group dance danced by ten dancers. The ten dancers are divided into four lean dancers, four jauk omang dancers, one telek dancer “Ni Swarni” and one jauk lingsir or Gore dancer. The Sesandaran dance at Griya Delod Pasar is built with eight dance structures, namely: Pepeson/Bebarisan, crewman, Pepeson Telek “Ni Swarni”, Pengecet, Pepeson Jauk Omang, Pepeson Gore/Jauk Lingsir, Pesiat and Pekaad. This dance has a function as an accompaniment to sacred performances or opening during the procession of mepajar or Ida Sesuhunan napak pertiwi. This Sesandaran dance contains four meanings, namely, religious meaning, creative meaning, aesthetic meaning and identity meaning